The Role of Entrepreneurial Passion in Mediating the Relationship between Entrepreneurial Intentions - Abwamiah, Nala; Setiawan, Rahyuniati; Mubarok, Teten Mohamad Sapril (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This research aims to find out how creativity influences entrepreneurial intentions through entrepreneurial passion of the age group 20 to 24 years in West Java Province. This research used a quantitative approach and the data collection method in this research was non-experimental or survey with a correlational research design. The population in this research was the age group 20 to 24 years in West Java Province and the sample in this research was 271 respondents processed using SmartPLS 3 software. The sampling technique in this research used probability sampling with a cluster random sampling type. The type of data in this research was interval with a semantic differential scale type. This research used the path analysis method. The results of this research show that Creativity influenced Entrepreneurial Intentions by 51.5 % . Creativity influenced Entrepreneurial Passion by 50.4 % . Entrepreneurial Passion influences Entrepreneurial Intentions by 19.3 % Creativity influenced Entrepreneurial Intentions through Entrepreneurial Passion by 9.7%.